NONTRADITIONAL METHOD OF CHEMICAL MODIFICATION OF THE SURFACE OF POROUS SILICA (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The main results obtained in the study of the possibility of low-temperature chemical modification of porous silica, applying various nanodispersed substances to their surface are given. It has been shown that the use of the chemical transport reaction (CTR) H2O2/ZnO for this purpose with the participation of H2O2 vapors at room temperature makes it possible to apply a number of oxides, sulfides and metal halides to the surface of various sorbents. An important advantage of the proposed modification method is that changes in the original texture parameters of the substrate are minimized. Using the example of modifying the behavior of highly pure SiO2 with zinc oxide, it was shown that the decomposition of gaseous intermediate products of CTR H2O2/ZnO occurs mainly in pores with a diameter of more than 6 nm.
Keywords: surface-modification; zinc oxide; chemical transport reaction; sorbents